Kohesi Sosial Sanro dan Guru dalam Memaksimalkan Fungsi Adat di Masyarakat Kabupaten Gowa (Equilibrium: Jurnal Pendidikan, 2019)
Sanitation social sanro and teachers in maximizing the function of adat to the community. Research Objective to analyze the relationship of sanro with teacher and various impacts. The type of research is descriptive qualitative with case study approach. Subjects in this study were sanro, teachers, community leaders and people among teenagers. The results of this study revealed that sanro social cohesion with teachers in maximizing the function of adat in the community of Gowa Regency, still preserving the culture or habit of hereditary every year is done as for the habit is kaddo minnya 'in the sense of preparing food at home daeng teacher (custom head), all the community participated in the procession of customary rituals performed after the prayer isya on Friday night when daeng teachers have implemented the ritual then all these foods are distributed to the community. Society assumes that this is a form of gratitude to the creator who has given reseki to his servant.Keywords: Social Cohesion, Customs, Culture